1983
DOI: 10.2118/83-05-02
|View full text |Cite
|
Sign up to set email alerts
|

Steamflood Performance In the Presence of Carbon Dioxide And Nitrogen

Abstract: The injection of mixtures of flue gas and steam has been pro-posed in conjunction with the development ofdownhole steam generators, the Vapor Therm process and the Wet Air Oxida-tion Boiler. The combined gas-steam injection process may be superior to steam-only injection in terms of improved oil pro-duction performance and reduced levels atmospheric pollu-tion. This paper reviews previous experimental and numerical simulation work related to gas-steam injection and presents the results of an experimental study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
16
0
5

Year Published

2002
2002
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 0 publications
1
16
0
5
Order By: Relevance
“…Harding et al, [1], among others). Phase behavior data have been obtained traditionally by experimental testing or by use of generalized correlations.…”
Section: Nomenclature 35mentioning
confidence: 95%
See 2 more Smart Citations
“…Harding et al, [1], among others). Phase behavior data have been obtained traditionally by experimental testing or by use of generalized correlations.…”
Section: Nomenclature 35mentioning
confidence: 95%
“…These methods are the most important thermal/miscible oil recovery processes (Wu, 1977 [5]; Harding et al;1983 [1]; Turek et al, 1984 [2], Boberg, 1988 [5]). Steam and/or CO 2 are injected into reservoirs where hydrocarbons and brines coexist.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Further recovery was reached when naphtha was added. Harding et al (1983) presented both experimental and simulation results suggesting that the coinjection of carbon dioxide or flue gas with steam yielded higher recoveries when compared to pure steam injection. Stone and Malcolm (1985) performed several tests to study the benefit of injecting carbon dioxide along with steam.…”
Section: Introductionmentioning
confidence: 99%
“…Naphtha increased recovery even further. Harding et al (2) showed that the co-injection of CO 2 or flue gas with steam yielded higher recoveries than pure steam injection.…”
Section: Introductionmentioning
confidence: 99%